Monitoring of Cardiorespiratory Parameters in Rats-Validation Based on Pharmacological Stimulation - Joanna Miklosz; Bartlomiej Kalaska; Stanislaw Zajaczkowski; Dariusz Pawlak; Andrzej Mogielnicki (MDPI AG, 2021)
The methods used in preclinical studies should minimize the suffering and the number of animals but still provide precise and consistent results enabling the introduction of drug candidates into the phase of clinical trials. Thus, we aimed to develop a method allowing us to perform preliminary safety and toxicity studies of candidates for human medicines, while reducing the number of animals. We have devised a method based on a combination of two devices: Plugsys (Transonics System Inc., Ithaca, NY, USA) and PhysioSuite (Kent Scientific Corporation, Torrington, CT, USA), which allow simultaneous registration of nine circulatory and respiratory parameters, and body temperature. Vehicle and adrenaline, or nitroglycerin, as reference substances were administered into the right femoral vein of Wistar rats. Physiological conditions were registered over 60 min after drug administration by measuring systolic, diastolic and mean blood pressure, heart rate (HR), blood perfusion of paw vessels, blood oxygen saturation, respiratory rate, average and peak exhaled CO2, and body temperature. Blood pressure was measured by cannula placed in the left common carotid artery and connected to the pressure transducer (Plugsys). The other parameters were measured by the PhysioSuite. Adrenaline-induced immediate dose-related hypertension and nitroglycerin hypotension were correlated with the change in blood perfusion. They both increased HR. Adrenaline decreased blood oxygen saturation and slightly affected respiratory parameters, while nitroglycerin caused a progressive increase in respiratory rate and a decrease in the peak of exhaled CO2. Our method may become an inseparable part of the preliminary safety and toxicity studies of tested drugs, while being an important step towards improving animal welfare.